Reliability Assessment of Steel-Lined and Prestressed FRC Slabs against Projectile Impact - Nadeem Siddiqui; Husain Abbas; Tarek Almusallam; Q. M. Li; Yousef Al-Salloum (Applied Sciences, 2022)
A simulation-based probabilistic method is proposed for assessing the reliability of steel-lined and prestressed fiber-reinforced concrete (PFRC) slabs against the impact loads. The impact testing of several prestressed and non-prestressed FRC slabs of 800 × 800 × 100 mm in size was carried out. The experimental program involved projectile impact testing of prestressed and non-prestressed FRC slabs using a gas gun. Three parameters were varied for testing of slabs under the projectile impact, viz., a quantity of steel fibers in the concrete, steel lining on the backside of the slab, and the prestressing level. The probability-based reliability analysis of all the tested specimens was then performed to highlight the influence of steel lining, steel fibers, and prestress in enhancing the safety of RC (reinforced concrete) slabs against projectile impacts. Projectile impact velocity exceeding the slab’s ballistic limit was assumed to lead to the failure of the PFRC slab, i.e., the perforation failure of the slab. Study results indicate that when no steel fiber was present, slab reliability was low. Adding fibers to slabs increases slabs’ reliability significantly. Specimens with the highest steel fiber content (1.2%) showed the greatest increase in reliability. The steel lining on the back face makes the slab’s reliability almost doubled in comparison with those without lining. Additionally, steel lining makes the PFRC slabs as reliable as desired. It was further noticed that the prestressing helps in enhancing the slab safety against projectile impacts. Even a minimal amount of prestressing makes a noticeable improvement in the reliability of PFRC slabs.